Tinjauan Ketepatan Pengkodean Penyakit pada Rekam Medis Pasien di Rumah Sakit Tk. III Dr. R. Soeharsono Banjarmasin - Apriyanti, Firda; Hermawan, Dedy; Annisa, Annisa (Jurnal Kesehatan Indonesia, 2024)
Medical recorders in assigning disease codes appropriately according to the classification applied in Indonesia use the International Statistical Classification of Diseases and Related Health Problems 10 (ICD-10) guidelines on diseases and medical actions in health services and management so that there are no errors in determining disease diagnoses and actions to be taken to patients. Determination of the diagnosis of the disease and the actions that will be taken to the patient. Based on preliminary studies conducted at the Tk. III Dr. R. Soeharsono Banjarmasin Hospital in January 2023, it was found that there were still incompletely written disease diagnoses and incorrect disease diagnosis codes with ICD-10. The purpose of this study was to determine the completeness of the writing of disease diagnoses and the accuracy of disease coding in patient medical records. This type of research is descriptive quantitative. The research design used a cross sectional approach. Sampling was carried out using purposive sampling method based on the number of patient medical records on January 2 - January 28, 2023 and obtained 96 patient medical records. Data collection methods using observation and questionnaires. The conclusion is that in 96 patient medical record files at the Tk. III Dr. R. Soeharsono Banjarmasin Hospital there are 12 incomplete diagnoses filled in and there are 3 incorrect disease diagnosis codes, the cause is because the diagnosis coder has never attended training related to coding competence.